Analysis of the Moral Value Found in Hamlet Based on Its Intrinsic Value - Elisa Ismitasari (Universitas Terbuka, 2023)
The potential teacher must study the broad subject, the subject of expertise, and the professional subject. Additionally, one of the proficiency courses is literature. The goal of this study,